Determination of metals concentrations and water quality status along Ulu Jempul River / Siti Norhafiza Mohd Khazaai …[et al.] - Mohd Khazaai, Siti Norhafiza; Amran, Siti Anis; Mohd Jan, Sarah Laila; Zakaria, Siti Raihan; Mat Hussin, Zurhana (2013)
This study was done to determine water quality status and heavy metals concentration along Ulu Jempul River. Samples from five sampling stations were analyzed two times which were on March and April 2013. Eight parameters were analyzed which were temperature, pH, Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD) by using YSI 556 MPS Handheld Water Quality Meter and two heavy metals which were Chromium and Zinc. Inductively Coupled Plasma-Mass Spectroscopy (ICP-MS) was applied to identify heavy metals concentration in the water samples for two difference weather conditions. Agricultural activities were the main causes for the water quality changes. One way analysis of variance (ANOVA) and Microsoft Excel was used to analyze data. The results obtained from ANOVA were compared with the stated value in Interim National Water Quality Standard (INWQS) to determine the river quality status. According to the Environmental Quality Act, 1974, the data collected was complying by the standard A. Almost all parameters showed no significant differences (P>0.05) for March and April for each station with confidence level of95% except for Dissolved Oxygen (DO) which was significant of P<0.05. Physico-chemical analysis along Ulu Jempul River at the five sampling stations was categorized under Class ll which is slightly polluted based on BOD values.